The Influence of Self-Regulated Learning on Resilience Among Senior High School Students of Tunas Harapan Mandiri Rantau Prapat - Sari, Nita Permata (Psikologi Prima, 2025)
This study aims to examine the influence of self-regulation in learning on students' resilience at SMA Tunas Harapan Mandiri Rantau Prapat. A quantitative method was used, with 166 students selected through random sampling from a total population of 200. The results showed a significant positive effect of self-regulation on student resilience, with a coefficient of rx2y = 18.072 and p = 0.000 (p < 0.01). The coefficient of determination (R²) was 0.870, indicating that 67.10% of students' resilience is influenced by their self-regulation in learning. Additionally, a significant positive relationship was found between self-regulation and peer social support on resilience (r = 0.894; p = 0.000). These findings suggest that the better students' self-regulation, the higher their resilience in facing academic challenges.